Hypercrosslinked polyionic liquid modified MXene nanocomposite as well as preparation method and application thereof

By chemically grafting vinylimidazole-based hyper-cross-linked polyionic liquids on MXene nanosheets, a hyper-cross-linked polyionic liquid-modified MXene composite adsorbent was prepared, which solved the problem of poor performance of MXene materials in adsorbing IBP pollutants and achieved Efficient, stable and selective adsorption effect.

CN119331184APending Publication Date: 2025-01-21DONGGUAN UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411568192.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing MXene materials exhibit poor adsorption performance when adsorbing non-steroidal anti-inflammatory organic pollutants such as IBP, and are easy to oxidize and stack, limiting their wide application in the field of adsorption.

Method used

By chemically grafting vinylimidazole-based hypercross-linked polyionic liquids on MXene nanosheets, a hypercross-linked polyionic liquid-modified MXene composite adsorbent (MXene-CPILs) was designed and prepared. The composite material utilizes the properties of the hypercross-linked polyionic liquid. The porous structure and high specific surface area of ​​MXene enhance the adsorption performance of IBP pollutants.

Benefits of technology

It achieves efficient adsorption of IBP pollutants, with a removal rate of up to 93.2%, while improving the stability and selectivity of the material, avoiding oxidation and stacking, and simplifying the recycling process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005119788290000011
    Figure HDA0005119788290000011
  • Figure HDA0005119788290000012
    Figure HDA0005119788290000012
  • Figure HDA0005119788290000013
    Figure HDA0005119788290000013
Patent Text Reader

Abstract

The invention relates to a hyper-crosslinked polyionic liquid modified MXene nano composite material as well as a preparation method and application thereof, and belongs to the field of nano functional materials. The invention relates to a preparation method of a hyper-crosslinked polyion liquid modified MXene nanocomposite, which comprises the following steps: dissolving vinylated MXene nanosheets and 1-vinyl-3-butylimidazolium bromide in toluene, adding styrene into the obtained solution, adding azodiisobutyronitrile, and reacting to obtain the polyion liquid modified MXene nanocomposite. Adding the obtained polyion liquid modified MXene composite material and dimethoxymethane into dichloroethane to uniformly disperse the polyion liquid modified MXene composite material, then adding anhydrous ferric trichloride into the solution, and reacting to obtain the hypercrosslinked polyion liquid modified MXene nano composite material. When the composite adsorbent provided by the invention is used for adsorbing the IBP, the highest removal rate can reach 93.2%, and the composite adsorbent is simple to operate, high in stability and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hyper-crosslinked polyionic liquid modified MXene nanocomposite material and a preparation method and application thereof, belonging to the field of nano functional materials. Background Art

[0002] Ibuprofen (IBP) is a typical non-steroidal anti-inflammatory drug with antipyretic, analgesic and anti-inflammatory effects, and is widely used around the world. IBP can enter the water environment through medical wastewater, pharmaceutical wastewater or farm wastewater. IBP in water bodies not only seriously affects the growth of aquatic plants and animals, but also seriously weakens the body's own immunity if consumed for a long time. Therefore, the efficient removal of IBP pollutants in water bodies is of great significance. Among the many removal methods, adsorption is widely used due to its simple operation, high removal efficiency and low cost.

[0003] Layered transition metal carbon / nitride (MXene) is an emerging two-dimensional nanomaterial with a unique two-dimensional layer structure, large specific surface area, good hydrophilicity and abundant surface active sites. It has shown great application potential in the field of adsorption. At present, MXene materials have excellent adsorption performance in the adsorption and removal of heavy metal and cationic dye pollutants. However, MXene is easy to oxidize, easy to restack and has a negative surface charge in water, resulting in poor adsorption and removal performance of non-steroidal anti-inflammatory drug organic pollutants such as IBP, which limits its further widespread application in the field of adsorption. Therefore, it is of great research significance to develop modified MXene adsorbents with high adsorption efficiency, good selectivity and strong stability for IBP.

[0004] Polyionic liquids (PILs) are polymers of ionic liquid monomers. They have both the unique properties of ionic liquids and the good mechanical properties of polymers, and are widely used in the field of adsorption and separation. Our team has designed a polyionic liquid-modified MXene nanosheet composite material for the adsorption and removal of chlorophenol compounds, which has good adsorption performance. However, the composite adsorbent has a relatively small area and cannot effectively and fully contact with organic pollutant molecules. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a hyper-crosslinked polyionic liquid modified MXene composite material, wherein the hyper-crosslinked polyionic liquid modified MXene composite material is a hyper-crosslinked poly(1-vinyl-3-butylimidazolium bromide) / MXene composite material. The composite material is based on the respective advantages of MXene materials and polyionic liquids in the field of adsorption, and utilizes the characteristics of easy functional modification of the surface of MXene nanosheets to design and prepare a hyper-crosslinked polyionic liquid grafted modified MXene composite adsorbent (MXene-CPILs). The composite adsorbent has the advantages of high adsorption efficiency, good selectivity and good stability for IBP organic pollutants.

[0006] A method for preparing a hyper-crosslinked polyionic liquid modified MXene nanocomposite material,

[0007] Preparation of polyionic liquid modified MXene composite material: vinylated MXene nanosheets and 1-vinyl-3-butyl imidazole bromide are dissolved in toluene, styrene is added to the above solution, and then azobisisobutyronitrile is added. After argon purging, the mixture is stirred and reacted at 40°C to 70°C for a period of time, filtered, washed, and dried to obtain a polyionic liquid modified MXene composite material. The MXene nanosheets are Ti 3 C 2 T x Nanosheets;

[0008] Preparation of hyper-crosslinked polyionic liquid modified MXene nanocomposite material: Add the obtained polyionic liquid modified MXene composite material and dimethoxymethane into dichloroethane to make the polyionic liquid modified MXene composite material evenly dispersed, then add anhydrous ferric chloride into the above solution, react at 60°C to 90°C for a period of time, extract the solid reaction product, and dry it to obtain a hyper-crosslinked polyionic liquid modified MXene nanocomposite material.

[0009] Preferably, in the preparation of the polyionic liquid modified MXene composite material, the mass ratio of vinylated MXene nanosheets to 1-vinyl-3-butylimidazolium bromide is 1:0.3 to 1:3; the ratio of vinylated MXene nanosheets to toluene is 1 g:150 to 200 mL; the mass ratio of azobisisobutyronitrile to vinylated MXene nanosheets is 1:0.05 to 1:4; the molar ratio of 1-vinyl-3-butylimidazolium bromide to styrene is 1:0.2 to 1:2.

[0010] Preferably, in the preparation of the polyionic liquid modified MXene composite material, after argon purging for 10 minutes, stirring and reacting at 40° C. to 70° C. for 12 hours to 48 hours, filtering, washing, and drying to obtain the polyionic liquid modified MXene composite material.

[0011] Preferably, in the preparation of the hyper-crosslinked polyionic liquid modified MXene nanocomposite material, the ratio of the polyionic liquid modified MXene composite material to ethylene dichloride is 1 g:160-240 mL; the ratio of the polyionic liquid modified MXene composite material to dimethoxymethane is 1 g:10-50 mL; the mass ratio of the polyionic liquid modified MXene composite material to anhydrous ferric chloride is 1:2-1:5.

[0012] Preferably, in the preparation of the hyper-crosslinked polyionic liquid modified MXene nanocomposite material, the reaction is carried out at 60° C. to 90° C. for 12 h to 48 h, the product is extracted with a mixed solution of methanol and acetic acid for 48 h, and then dried to obtain a hyper-crosslinked polyionic liquid modified MXene nanocomposite material.

[0013] Preferably, the vinylated MXene nanosheets are prepared by the following method: Ti 3 C 2 T x Nanosheets and vinyl triethoxysilane are added to toluene in a mass ratio of 1:1 to 1:5, reacted at 50 to 100°C for 12 to 48 hours, washed with ethanol and deionized water three times, and vacuum dried to obtain vinyl MXene nanosheets, wherein Ti 3 C 2 T x The ratio of nanosheets to toluene is 1 g:50-100 mL.

[0014] Another object of the present invention is to provide a hyper-crosslinked polyionic liquid modified MXene nanocomposite material prepared by the above method.

[0015] The hyper-crosslinked polyionic liquid modified MXene nanocomposite material of the present invention has a fluffy surface and a porous structure.

[0016] The super-crosslinked polyionic liquid modified MXene nanocomposite material obtained by the present invention is a super-crosslinked polyionic liquid of vinyl imidazole chemically grafted on a MXene nanosheet, and the super-crosslinked polyionic liquid has a rich and stable pore structure.

[0017] Another object of the present invention is to provide the use of the obtained hyper-crosslinked polyionic liquid modified MXene nanocomposite as an ibuprofen adsorbent.

[0018] A method for adsorbing ibuprofen in organic wastewater comprises contacting the hyper-crosslinked polyionic liquid modified MXene nanocomposite material with organic wastewater containing ibuprofen for a certain period of time.

[0019] The beneficial effects of the present invention are as follows: the present invention chemically grafts a vinyl imidazole-based hyper-crosslinked polyionic liquid onto the MXene nanosheet, and the hyper-crosslinked polyionic liquid has a rich and stable pore structure, increases the specific surface area and is conducive to the full exposure of the adsorption active sites; the present invention introduces a benzene ring as a crosslinking site in the polyionic liquid segment, which is conducive to the construction of a hyper-crosslinked porous structure. The polyionic liquid carries a large number of positively charged imidazole rings, which provide a variety of adsorption forces such as electrostatic action, hydrogen bonding and π-π action to IBP pollutants, which greatly improve the adsorption performance of MXene materials for IBP pollutants. In addition, the introduction of the hyper-crosslinked polyionic liquid hinders the stacking of MXene nanosheets, inhibits the oxidation of MXene, and also improves the problem that MXene nanosheets are difficult to separate and recycle. The composite adsorbent provided by the present invention is used to adsorb IBP, and its removal rate can reach up to 93.2%, and it is simple to operate, stable and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a SEM image of the MXene nanosheets prepared in Example 4 of the present invention.

[0021] Figure 2 This is a SEM image of MXene-CPILs synthesized in Example 4 of the present invention.

[0022] Figure 3 It is the removal rate of the composite materials prepared by Examples 1 to 6 of the present invention and Comparative Examples 1 and 2 for the IBP aqueous solution with a concentration of 10 mg / L. Figure 3 It can be seen that the removal rate of IBP by the composite material prepared in Example 4 is as high as 93.2%. DETAILED DESCRIPTION

[0023] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0024] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0025] A preferred technical solution of the present invention is:

[0026] A method for preparing a hyper-crosslinked polyionic liquid modified MXene nanocomposite material comprises the following steps:

[0027] (1) Preparation of vinyl MXene nanosheets: Ti 3 C 2 T x Nanosheets and vinyl triethoxysilane are added to toluene in a mass ratio of 1:1 to 1:5, wherein Ti 3C 2 T x The ratio of nanosheets to toluene is 1 g: 50-100 mL, the reaction is carried out at 50-100 °C for 12-48 h, and the product is washed three times with ethanol and deionized water in sequence. Finally, the product is vacuum dried to obtain vinylated MXene nanosheets.

[0028] (2) Synthesis of polyionic liquid modified MXene composites: Vinyl Ti 3 C 2 T x Nanosheets and 1-vinyl-3-butyl imidazole bromide are added to toluene in a mass ratio of 1:0.3 to 1:3, wherein the vinyl Ti 3 C 2 T x The ratio of nanosheets to toluene is 1 g: 150-200 mL, styrene is added at a molar ratio of 1-vinyl-3-butyl imidazole bromide to styrene of 1:0.2-1:2, and the reaction is stirred for 10 minutes, and azobisisobutyronitrile and vinyl Ti ​​are added. 3 C 2 T x The nanosheets are added to the above solution at a mass ratio of 1:0.05 to 1:4, argon gas is purged for 10 minutes, the reaction time is 12 hours to 48 hours, the reaction temperature is 40°C to 70°C, and the product is vacuum dried to obtain a polyionic liquid modified MXene composite material.

[0029] (3) Preparation of hyper-crosslinked polyionic liquid modified MXene composite materials (MXene-CPILs): The ratio of polyionic liquid modified MXene composite materials to ethylene dichloride is 1 g: 160-240 mL, and the ratio of polyionic liquid modified MXene composite materials to dimethoxymethane is 1 g: 10-50 mL. The three are mixed and stirred evenly. Anhydrous ferric chloride is added to the above solution at a mass ratio of 1:2-1:5 between the polyionic liquid modified MXene composite materials and anhydrous ferric chloride. The reaction time is 12 h-48 h, and the reaction temperature is 60°C-90°C. The product is extracted with a mixed solution of methanol and acetic acid for 48 h, and then dried under vacuum at 60°C for 24 h to obtain a hyper-crosslinked polyionic liquid modified MXene composite material.

[0030] Example 1

[0031] (1) 1gTi 3 C 2 T x The nanosheets and 1 g of vinyl triethoxysilane were added to 50 mL of toluene and reacted at 60 °C for 12 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0032] (2) Add 1 g of vinylated MXene nanosheets and 1 g of 1-vinyl-3-butyl imidazole bromide to 150 mL of toluene. After stirring and dissolving, add styrene to the above solution at a molar ratio of vinylated MXene to styrene of 1:0.2, and then add azobisisobutyronitrile to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:0.05. Purge argon for 10 min and stir at 50 ° C for 24 h. Vacuum dry at 60 ° C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0033] (3) The polyionic liquid modified MXene composite material and dichloroethane were added to the reaction bottle in a ratio of 1 g:160 mL, and then dimethoxymethane was added in a ratio of 1 g:10 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added to the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:2. The reaction was carried out at 60°C for 12 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0034] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and adsorb at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene-CPILs reached 60.8%.

[0035] Example 2

[0036] (1) 1gTi 3 C 2 T x The nanosheets and 3 g of vinyl triethoxysilane were added to 80 mL of toluene and reacted at 50 °C for 12 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0037] (2) Add 1 g of vinylated MXene nanosheets and 2 g of 1-vinyl-3-butyl imidazole bromide to 160 mL of toluene. After stirring and dissolving, styrene is added to the above solution at a molar ratio of vinylated MXene to styrene of 1:0.5, and then azobisisobutyronitrile is added to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:2. Purge argon for 10 min and stir at 40 °C for 12 h. Vacuum dry at 60 °C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0038] (3) The polyionic liquid modified MXene composite material and dichloroethane were added to the reaction bottle in a ratio of 1 g:180 mL, and then dimethoxymethane was added in a ratio of 1 g:20 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added to the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:5. The reaction was carried out at 70°C for 24 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0039] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and adsorb at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene-CPILs reached 67.1%.

[0040] Example 3

[0041] (1) 1gTi 3 C 2 T x The nanosheets and 2 g of vinyl triethoxysilane were added to 60 mL of toluene and reacted at 100 °C for 24 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0042] (2) Add 1 g of vinylated MXene nanosheets and 0.3 g of 1-vinyl-3-butyl imidazole bromide to 170 mL of toluene. After stirring and dissolving, styrene is added to the above solution at a molar ratio of vinylated MXene to styrene of 1:0.6, and then azobisisobutyronitrile is added to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:1. Purge argon for 10 min and stir at 50 ° C for 48 h. Vacuum dry at 60 ° C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0043] (3) The polyionic liquid modified MXene composite material and dichloroethane were added into the reaction bottle in a ratio of 1 g:200 mL, and then dimethoxymethane was added in a ratio of 1 g:40 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added into the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:3. The reaction was carried out at 70°C for 48 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0044] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and adsorb at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene-CPILs reached 72.7%.

[0045] Example 4

[0046] (1) 1gTi 3 C 2 T x The nanosheets and 5 g of vinyl triethoxysilane were added to 70 mL of toluene and reacted at 80 °C for 24 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0047] (2) Add 1 g of vinylated MXene nanosheets and 1.5 g of 1-vinyl-3-butyl imidazole bromide to 150 mL of toluene. After stirring and dissolving, add styrene to the above solution at a molar ratio of vinylated MXene to styrene of 1:1, and then add azobisisobutyronitrile to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:4. Purge argon for 10 min and stir at 65 °C for 30 h. Dry under vacuum at 60 °C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0048] (3) The polyionic liquid modified MXene composite material and dichloroethane were added into the reaction bottle in a ratio of 1 g:200 mL, and then dimethoxymethane was added in a ratio of 1 g:25 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added into the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:5. The reaction was carried out at 80°C for 24 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0049] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and oscillate and adsorb at 200 rpm / min for 6 h at room temperature. The removal rate of IBP by MXene-CPILs reached 93.2%.

[0050] Example 5

[0051] (1) 1gTi 3 C 2 T xThe nanosheets and 3 g of vinyl triethoxysilane were added to 70 mL of toluene and reacted at 90 °C for 24 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0052] (2) Add 1 g of vinylated MXene nanosheets and 1 g of 1-vinyl-3-butyl imidazole bromide to 200 mL of toluene. After stirring and dissolving, add styrene to the above solution at a molar ratio of vinylated MXene to styrene of 1:2, and then add azobisisobutyronitrile to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:2. Purge argon for 10 min and stir at 70 °C for 12 h. Dry under vacuum at 60 °C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0053] (3) The polyionic liquid modified MXene composite material and dichloroethane were added to the reaction bottle in a ratio of 1 g:240 mL, and then dimethoxymethane was added in a ratio of 1 g:50 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added to the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:4. The reaction was carried out at 90°C for 12 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0054] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and adsorb at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene-CPILs reached 84.2%.

[0055] Example 6

[0056] (1) 1gTi 3 C 2 T x The nanosheets and 4 g of vinyl triethoxysilane were added to 60 mL of toluene and reacted at 60 °C for 12 h. The product was washed three times with ethanol and deionized water. Finally, the product was vacuum dried to obtain vinylated MXene nanosheets.

[0057] (2) Add 1 g of vinylated MXene nanosheets and 3 g of 1-vinyl-3-butyl imidazole bromide to 170 mL of toluene. After stirring and dissolving, styrene is added to the above solution at a molar ratio of vinylated MXene to styrene of 1:0.5, and then azobisisobutyronitrile is added to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:4. Purge argon for 10 min and stir at 60 ° C for 48 h. Vacuum dry at 60 ° C for 24 h to obtain a polyionic liquid 000 modified MXene composite material.

[0058] (3) The polyionic liquid modified MXene composite material and dichloroethane were added to the reaction bottle in a ratio of 1 g:200 mL, and then dimethoxymethane was added in a ratio of 1 g:30 mL. The three were ultrasonically dispersed and stirred for 30 minutes. Then, anhydrous ferric chloride was added to the above solution in a mass ratio of anhydrous ferric chloride to dimethoxymethane of 1:4. The reaction was carried out at 65°C for 24 hours. The product was extracted with a mixed solution of methanol and acetic acid for 48 hours, and then vacuum dried at 60°C for 24 hours to obtain a MXene-CPILs composite material.

[0059] (4) Accurately weigh 10 mg of the composite adsorbent MXene-CPILs, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and adsorb at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene-CPILs reached 73.1%.

[0060] Comparative Example 1

[0061] (1) First, add 50 mL of 40% HF aqueous solution into the reaction bottle, weigh 5 g Ti 3 AlC 2 The powder was slowly added to the reaction bottle and stirred for 30 minutes. The reaction was continued at 35°C for 24 hours. The product was washed 5 to 9 times by centrifugation with deionized water, then subjected to ultrasonic stripping for 30 minutes and shaken on a shaker for 48 hours. Finally, the gel was freeze-dried to obtain Ti 3 C 2 T x MXene nanosheets.

[0062] (2) Accurately weigh 10 mg Ti 3 C 2 T x MXene nanosheets, 10 mL of 10 mg / L IBP aqueous solution were mixed evenly, and adsorbed at room temperature at 200 rpm / min for 6 h. The removal rate of IBP by MXene reached 4.3%.

[0063] Comparative Example 2

[0064] (1) Add 1 g of vinylated MXene nanosheets and 1.5 g of 1-vinyl-3-butyl imidazole bromide to 160 mL of toluene. After stirring and dissolving, add styrene to the above solution at a molar ratio of vinylated MXene to styrene of 1:1, and then add azobisisobutyronitrile to the above solution at a mass ratio of azobisisobutyronitrile to vinylated MXene of 1:4. Purge argon for 10 min and stir at 65 °C for 30 h. Vacuum dry at 60 °C for 24 h to obtain a polyionic liquid modified MXene composite material.

[0065] (2) Accurately weigh 10 mg of polyionic liquid modified MXene composite adsorbent, take 10 mL of 10 mg / L IBP aqueous solution, mix the two evenly, and oscillate and adsorb at 200 pm / min for 6 hours at room temperature. The removal rate of IBP by polyionic liquid modified MXene composite material reaches 57.5%.

Claims

1. A method for preparing a hyper-crosslinked polyionic liquid modified MXene nanocomposite material, characterized in that: Preparation of polyionic liquid modified MXene composite material: vinylated MXene nanosheets and 1-vinyl-3-butyl imidazole bromide are dissolved in toluene, styrene is added to the above solution, and then azobisisobutyronitrile is added. After argon purge, the mixture is stirred and reacted at 40°C to 70°C for a period of time, filtered, washed, and dried to obtain a polyionic liquid modified MXene composite material. The MXene nanosheet is Ti3C2T x Nanosheets; Preparation of hyper-crosslinked polyionic liquid modified MXene nanocomposite material: Add the obtained polyionic liquid modified MXene composite material and dimethoxymethane into dichloroethane to make the polyionic liquid modified MXene composite material evenly dispersed, then add anhydrous ferric chloride into the above solution, react at 60°C to 90°C for a period of time, extract the solid reaction product, and dry it to obtain a hyper-crosslinked polyionic liquid modified MXene nanocomposite material.

2. The method according to claim 1, characterized in that: In the preparation of the polyionic liquid modified MXene composite material, the mass ratio of vinylated MXene nanosheets to 1-vinyl-3-butylimidazolium bromide is 1:0.3 to 1:3; the ratio of vinylated MXene nanosheets to toluene is 1 g:150 to 200 mL; the mass ratio of azobisisobutyronitrile to vinylated MXene nanosheets is 1:0.05 to 1:4; and the molar ratio of 1-vinyl-3-butylimidazolium bromide to styrene is 1:0.2 to 1:

2.

3. The method according to claim 1 or 2, characterized in that: In the preparation of the polyionic liquid modified MXene composite material, after argon purging for 10 minutes, stirring and reacting at 40° C. to 70° C. for 12 hours to 48 hours, filtering, washing, and drying to obtain the polyionic liquid modified MXene composite material.

4. The method according to claim 1, characterized in that: In the preparation of the hyper-crosslinked polyionic liquid modified MXene nanocomposite material, the ratio of the polyionic liquid modified MXene composite material to ethylene dichloride is 1 g: 160-240 mL; the ratio of the polyionic liquid modified MXene composite material to dimethoxymethane is 1 g: 10-50 mL; the mass ratio of the polyionic liquid modified MXene composite material to anhydrous ferric chloride is 1:2-1:

5.

5. The method according to claim 1 or 4, characterized in that: In the preparation of the hyper-crosslinked polyionic liquid modified MXene nanocomposite material, the reaction is carried out at 60° C. to 90° C. for 12 h to 48 h, the product is extracted with a mixed solution of methanol and acetic acid for 48 h, and then dried to obtain the hyper-crosslinked polyionic liquid modified MXene nanocomposite material.

6. The method according to claim 1, characterized in that The vinylated MXene nanosheets were prepared as follows: Ti3C2T x Nanosheets and vinyl triethoxysilane are added to toluene in a mass ratio of 1:1 to 1:5, reacted at 50 to 100 °C for 12 to 48 hours, washed with ethanol and deionized water three times, and vacuum dried to obtain vinyl MXene nanosheets, wherein Ti3C2T x The ratio of nanosheets to toluene is 1 g:50-100 mL.

7. A hyper-crosslinked polyionic liquid modified MXene nanocomposite material prepared by the method according to any one of claims 1 to 6.

8. Use of the hyper-crosslinked polyionic liquid modified MXene nanocomposite material according to claim 7 as an ibuprofen adsorbent.

9. A method for adsorbing ibuprofen in organic wastewater, characterized in that: The hyper-crosslinked polyionic liquid modified MXene nanocomposite material according to claim 7 is contacted with organic wastewater containing ibuprofen for a certain period of time.

Citation Information

Cited By

  • Antibacterial moisture-permeable polyester material and preparation method thereof

    CN120554814A